2016
DOI: 10.1620/tjem.240.167
|View full text |Cite
|
Sign up to set email alerts
|

A Term Infant of Neonatal Toxic Shock Syndrome-Like Exanthematous Disease Complicated with Hemophagocytic Syndrome

Abstract: Neonatal toxic shock syndrome-like exanthematous disease (NTED) is a newly recognized neonatal infectious disease, caused by the superantigen toxic shock syndrome toxin-1 (TSST-1). TSST-1 is mainly produced by methicillin-resistant Staphylococcus aureus, and the immune responses to TSST-1 are known to cause toxic shock syndrome, a life-threatening infectious disease. The clinical symptoms of NTED are skin rash, fever, and thrombocytopenia, but severe thrombocytopenia is rare in term infants with NTED. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Studies were excluded if they did not discuss nHLH ( n = 280); aggregated nHLH patient data with all ages ( n = 83); provided insufficient detail and/or data describing a case of nHLH ( n = 28); and for other reasons ( n = 8). Two‐hundred‐five cases of nHLH from 142 articles were included in our analysis 12–152 …”
Section: Resultsmentioning
confidence: 99%
“…Studies were excluded if they did not discuss nHLH ( n = 280); aggregated nHLH patient data with all ages ( n = 83); provided insufficient detail and/or data describing a case of nHLH ( n = 28); and for other reasons ( n = 8). Two‐hundred‐five cases of nHLH from 142 articles were included in our analysis 12–152 …”
Section: Resultsmentioning
confidence: 99%
“…TSS in neonates is relatively a newly recognized neonatal infectious disease, although it was first described by Todd et al in 1978 in previously healthy children [ 13 , 14 ]. There are limited data describing epidemiology, management, and outcomes for children with TSS [ 1 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observation of hemophagocytic macrophages in a peripheral blood smear is uncommon. Kaga et al 6) reported a neonate with neonatal toxic shock syndrome (TSS) -like exanthematous disease (NTED) complicated by hemophagocytic syndrome (HPS). In this case, the patient did not meet the diagnostic criteria of HPS, socalled hemophagocytic lymphohistiocytosis (HLH).…”
Section: Discussionmentioning
confidence: 99%